THE RISE OF MULTINATIONAL CORPORATION AND THE DEAD OF INNOVATION - Muh. Sholihin (As-Salam: Jurnal Studi Hukum Islam & Pendidikan, 2013)
The article presents the rise of multinational corporation effect toward innovation in globalization era and how islamic economics views them—as an alternative perspective in analyzing this problem. “The rise of multinational corporatian reduces the product innovation”. It is a assumption and appears as an interpretation to market-mechanism. The thesis will elaborate in the paper. It means that innovation reduction is caused by multinational corporation product following market trend. The thesis, indeed, corrobates John Xiros Cooper’s theory. “The market is simply an economic mechanism which has no extraordinary powers to shift the ground of thinking and knowing in any general sense. It is merely, they will say, a mechanism for allocating resources among producers, a mechanism for the setting of commodity prices, for distributing goods, for adding value, for raising capital to sustain enterprise, and so on.” Wrote Xiros Cooper. To understand the reason why multinational corporation rising makes innovation weak will use sociological approach, especially epistemology of market—Xiros Cooper theory.